Knowledge and Smoking Behavior Among High School Students : A Cross-Sectional Study - Dendi Dendi; Handika Pramudya; Mila Sartika; Hana Priscilla Frudence Sohilait (STIKep PPNI Jawa Barat, 2025)
Background: Smoking involves the combustion of tobacco products, producing smoke that is inhaled by the smoker and can also be passively inhaled by individuals in the surrounding environment. Adolescence is a vulnerable period during which smoking behaviors may develop, influenced by knowledge, attitudes, and social factors. Limited awareness of the health risks associated with smoking may contribute to the persistence of smoking behavior among adolescents. Objective: This study aimed to examine the relationship between knowledge and smoking-related behavior among adolescent students at State Senior High School 3 Tambun Selatan in 2025. Methods: A quantitative study with a descriptive correlational design and a cross-sectional approach was conducted. The study population consisted of all male students enrolled at State Senior High School 3 Tambun Selatan (n = 452). A total of 440 respondents participated in the study. Data collection was carried out on January 31, 2025, using structured questionnaires. Statistical analysis was performed using the Chi-square test to assess associations between variables. Results: The analysis revealed a statistically significant relationship between adolescents’ knowledge and smoking behavior (p = 0.005). In addition, a significant association was found between behavioral factors and smoking incidence (p < 0.001), indicating that lower knowledge levels and unfavorable behaviors were associated with higher smoking prevalence. Conclusion: This study demonstrates that adolescents’ knowledge and behavior are significantly associated with smoking habits. Strengthening school-based health education programs focusing on the dangers of smoking is essential to reduce smoking prevalence and promote healthier behaviors among adolescents